"Hell was let loose on the country": The Social History of Military Technology in the Republic of Biafra. (2nd July 2018) - Daly, Samuel Fury Childs
Abstract: The problem of armed crime in late twentieth-century Nigeria was closely connected to the events of the Nigerian Civil War (1967–1970). Legal records from the secessionist Republic of Biafra reveal how violent crime emerged as part of the military confrontation between Biafra and Nigeria. The wide availability of firearms, the Biafran state's diminishing ability to enforce the law, and the gradual collapse of Biafra's economy under the pressure of a Nigerian blockade made Biafran soldiers and civilians reliant on their weapons to obtain food and fuel, make claims to property, and settle disputes with one another. Criminal legal records illustrate how military technologies shape interactions and relationships in the places where they are deployed, and how those dynamics can endure after the war comes to an end. This speaks to larger theoretical questions about the symbolic and functional meanings of guns during and after wartime. Résumé: Le problème des crimes armés au Nigeria à la fin du XXe siècle a été étroitement lié aux événements de la guerre civile nigériane entre 1967 & 1970. Les documents juridiques de la République du Biafra sécessionniste révèlent comment les crimes violents ont émergé dans le cadre de l'affrontement militaire entre le Biafra et le Nigeria. La large disponibilité d'armes à feu, la capacité diminuer du Biafra de faire respecter la Loi et l'effondrement progressif de son économie sous la pression d'un blocus nigérian ont rendu civils et soldats du Biafra tributaire de leurs armes pour obtenir vivres et carburant, ainsi que faire des revendications de propriété et régler les différends entre eux. Les casiers judiciaires sous étude illustrent comment les technologies militaires forment les interactions et les relations dans les endroits où elles sont utilisées et de quelle manière cette dynamique perdure après que la guerre soit achevée. Cette exploration soulève des questions théoriques plus vastes sur la signification symbolique et fonctionnelle des armes pendant et après la guerre.